การสูบบุหรี่กับการเกิดโรคหลอดเลือดหัวใจ: บทบาทของพยาบาลในการช่วยเลิกบุหรี่ - คำรัตน์, จิรภิญญา; มีสุขมาก, ณภัทรชนม์ (Journal of The Royal Thai Army Nurses, 2017)
การสูบบุหรี่เป็นหนึ่งในปัจจัยสำคัญของการเกิดโรคหลอดเลือดหัวใจซึ่งเป็นโรคไม่ติดต่อเรื้อรังที่สำคัญโรคหนึ่งที่กำลังคร่า ชีวิตคนไทยอยู่ในปัจจุบัน การทราบถึงพิษภัยและผลกระทบที่เกิดจากการสูบบุหรี่ต่อหลอดเลือดหัวใจจะช่วยให้ประชาชนตระหนัก ถึงอันตรายของบุหรี่ที่มีต่อสุขภาพและเห็นความสำคัญของการไม่สูบบุหรี่หรือเลิกสูบบุหรี่เพื่อลดความรุนแรงที่เกิดจากการสูบบุหรี่ ต่อโรคหลอดเลือดหัวใจในอนาคต บทความนี้มีวัตถุประสงค์เพื่ออธิบายความสัมพันธ์ระหว่างการสูบบุหรี่และการเกิดโรคหลอดเลือด หัวใจรวมถึงบทบาทของพยาบาลในการช่วยเลิกบุหรี่ อันจะนำไปสู่การตระหนักรู้ในเรื่องการเกิดโรคหลอดเลือดหัวใจซึ่งเป็นผลมา จากการสูบบุหรี่และเพื่อใช้เป็นแนวทางสำหรับบุคลากรทางสุขภาพในการช่วยเลิกบุหรี่ในผู้ป่วยโรคหลอดเลือดหัวใจต่อไป Cigarettes Smoking and Coronary Artery Disease: Nurses’ Role in Smoking Cessation Cigarette smoking is one of the leading causes of coronary artery disease (CAD), which is one of the important of non-communicable diseases (NCDs) and currently kills Thai people. In order to promoted health and prevented CAD, knowledge about harmful effect of cigarette smoking on coronary artery disease can encourage people to realize on non-smoking or quit smoking. Therefore, this article aimed to describe about relationship between cigarette smoking and coronary artery disease involving nurses’ role in smoking cessation. It can lead to awareness about the development of CAD affect from smoking and it can use as a guideline for health care professionals in order to help patients with CAD stop smoking.